American Sign Language for Science Terminology in Fourth Grade Elementary School - Ni Wayan Astri Antari; Putu Nanci Riastini; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2025)
The limitations of Kata Kolok sign language for science terminology require an equivalent of American Sign Language (ASL). Therefore, this research aims to investigate the number of science terminology for grade IV elementary school and explore the availability of American Sign Laguange (ASL) for science terminology for grade IV elementary school. This type of research is descriptive research. The subject of this research is science terminology for grade IV elementary school. Then, the object of this research is the availability of science terminology for grade IV elementary school and American Sign Language (ASL). The data collection used is in the form of a check-list sheet. The data analysis method uses descriptive statistical analysis with Mean and Percentage calculations. The results of this research were that 101 word terms and 106 science phrase terms for grade IV elementary school were successfully identified and were appropriate to the science context. Furthermore, the results obtained were 89 word terms and 15 phrase terms available in the ASL dictionary. The percentage of word terminology available in the ASL dictionary is 88% in the very high category, while for phrase terminology it is 14% in the very low category. Recommendations from the results of this research can be documented in database form and developed into sign language-based products, so as to realize inclusive learning.